Comparative metabolome profiling of two contrasting wheat cultivars in late-season water deficit - Saeidi, Mohsen; Ahmadi, Ali; Moradi, Foad; Hajirezaei, Mohammad-Reza (Frontiers in Plant Physiology, 2024)
Abiotic stresses, including water deficit, cause myriad changes in plant metabolism. Metabolomics is a powerful tool for understanding plant resistance to such stresses. Therefore, this research was conducted to evaluate the effects of after anthesis water deficit (WD: from anthesis to maturity), i.e., maintaining moisture at field capacity (well-watered: WW) and 50% field capacity, on metabolome profiling (amino acids, hormones, nucleotides, soluble and insoluble sugars, sugar alcohols, and enzymes) in grains of two contrasting wheat cultivars grown in a greenhouse at Razi University as a factorial experiment. Based on the results, WD decreased grain yield (57%), 1000 grain weight (50%), and grain plant-1 (9%) in the sensitive cultivar (SC), while it had no significant effect on the tolerant cultivar (TC). In WW, the concentration of IAA, glucose, and fructose, as well as the activity of three invertase isoforms (vacuolic, cytosolic, and cell wall bound), were significantly higher at 10 days after anthesis compared to 17 and 31 days. In WD, these traits were significantly reduced in SC. ABA and sucrose concentration and sucrose synthase activity were significantly higher 17 days after anthesis than 10 days after anthesis. WD. In contrast to ABA, sucrose concentration decreased significantly in growing grains of SC in WD. The ATP/ADP ratio, inositol, glycerol and erythritol contents of TC were significantly higher in WD than in SC. Among the different amino acids, asparagine, glutamine and lysine were the highest, while ACC and methionine were the lowest. Contrary to SC, WD significantly increased the sum of the amino acid concentrations determined in the grains of TC, i.e. asparagine (22%), aspartic acid (48%), glycine (48%), ACC (79%) and valine (133%). These findings could help us to understand the resistance mechanisms to late season water deficit, which can increase sink strength (sink size and sink activity) and achieve higher yield quantity and quality in wheat.